Turning mannitol-rich agricultural waste to poly(3-hydroxybutyrate) with Cobetia amphilecti fermentation and recovery with methyl levulinate as a green solvent. (May 2022) - Gnaim, Rima; Unis, Razan; Gnayem, Nabeel; Das, Jagadish; Gozin, Michael; Golberg, Alexander
Graphical abstract: Highlights: C. amphilecti strain isolated from Ulva sp. was used for the biosynthesis of PHB. PHB was generated from mannitol-rich agriculture wastes by C. amphilecti. Methyl levulinate is a novel renewable and non-chlorinated PHB extraction solvent. High recovery yield and purity of PHB were obtained with methyl levulinate solvent. Abstract: The present study explored the use of mannitol and mannitol-rich agro-industrial wastes as substrates for PHB production by Cobetia amphilecti isolated from the green Ulva sp. seaweed. Cultivation of C. amphilecti on mannitol, celery, and olive leaves (OLs) waste led to 4.20, 6.00, and 5.16 g L −1 of cell dry mass (CDM), 76.3, 25.5, and 12.0% of PHB content in CDM and 3.2, 1.53, and 0.62 g L −1 of PHB concentration, respectively; which suggested that they can be exploited as carbon substrates for the production of PHB. Extraction of PHB from C. amphilecti cultures by solubilization in the green solvent methyl levulinate (ML) (2% w/w, 140 °C, 1 h) indicated that the recovery yield and purity of PHB are above 97 and 90% w/w, respectively. The use of ML could be an attractive method for the recovery of PHB when safe and non-toxic solvents are required.